PENGARUH KEPEMIMPINAN DAN MOTIVASI KEPALA SEKOLAH TERHADAP KEPUASAN KERJA GURU DI SEKOLAH DASAR NEGERI KECAMATAN TEBAS - Akhmadi, Akhmadi; Asmara, Urai Husna; Aswandi, Aswandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The general problem raised in this study is whether the leadership of the principal has a significant effect on job satisfaction, does the principal's motivation significantly influence the teacher's job satisfaction, and or does the principal's leadership and motivation affect teachers' job satisfaction equally?The regression test results from independent variables to the dependent variable obtained data of 39.7% and 33.2% respectively and together independent variables to the dependent variable 68%. Thus it is stated that there is a significant influence between the independent variables on the dependent variable. Other data that support is that the results of F arithmetic on Anova b 21, 737 is greater than F table is 3.04 and accepted.Based on the above data can be summed up as follows:The category of job satisfaction satisfy with the frequency distribution of respondents Of 203 samples or 40.39%. Headmaster leadership categories with frequency distribution 81 Respondents from 203 samples or 39.90%. High school principal motivation with frequency distribution of 81 respondents rom203 samples or 39.90%.The leadership of the principal influences significantly Teacher's job satisfaction in SD Negeri Kecamatan Tebassebesar 39,7%. The motivation of the principal has an effect on the satisfaction of teachers of SD Negeri Tebas sub-district is significantly 33,2%. Headmaster's leadership and principal motivation together-The same effect on the job satisfaction of elementary school teachers Tebas District Significantly by 68%. Key Words: Principal Leadership, Principal Motivation, and Master's Job Satisfaction.